Effect of SGLT-2 Inhibitor Therapy on Cardiovascular Health in Diabetes Mellitus Patients - Gusti Destiana (Global Health Science Group, 2020)
Cardiovascular disease has become a major cause of mortality and morbidity in patients with type 2 diabetes mellitus. The main factors that increase the risk of cardiovascular disease include chronic hyperglycemia, decreased insulin sensitivity, visceral adiposity, and particularly hypertensive comorbidity and increased arterial stiffness. Meanwhile, sodium-glucose co-transporter-2 inhibitors, a new category in diabetes therapy are known to reduce blood glucose in patients by increasing glycosuria through inhibition of urinary glucose reabsorption. The therapy also produces glucose-induced osmotic diuresis, weight loss, and lowered blood pressure. The aim of this literature review is to determine the effect of sodium-glucose co-transporter-2 inhibitors on cardiovascular health in diabetes mellitus patients. This study is a literature review involving 20 literature sources from 3 national journals and 17 international journals with the keywords used include diabetes mellitus, cardiovascular and SGLT-2 inhibitors. Several studies have significantly demonstrated the effect of SGLT-2 inhibitors on cardiovascular health, as seen by a reduction in mortality and hospitalization of heart failure, better blood pressure and renal outcome, improved heart function in diabetic cardiomyopathy and myocardial ischemia.